Infecções com baixas doses de Leishmania amazonensis: um modelo para o estudo de leishmania tegumentar americana - Denise Fonseca Cortes (2008)
A model of infection with Leishmania amazonensis in the skin, with low doses of parasites, was compared to infection with high doses of L. amazonensis and low and high doses of L. major. C57BL/6 mice were infected with 103 or 106 parasites in the ear and the outcome of infection was assessed. The appearance of lesions in mice infected with 103 parasites was delayed compared to mice infected with 106 Leishmania and parasites were detectable at the infection site even before lesions were. Mice infected with L. amazonensis displayed persistent lesions, while infection with L. major spontaneously healed in all groups, albeit lymphocytes persisted at the site of infection even after healing. Macrophages persisted only in L. amazonensis-infected mice. L. amazonensis infected mice produced lower levels of IFN-ã than mice infected with L. major. No correlation between persistence of parasites and IL-10 levels or the production of nitric oxide or activity of arginase by macrophages was found. We conclude that infection with low doses of L. amazonensis in the dermis changes the course of infection by delaying the appearance of lesions, but does not change the outcome of susceptibility and cytokine production described for the subcutaneous infection with high numbers of parasites.